Fanatismo Religioso Un Acercamiento Psicoanalítico Sobre Los Factores Inconscientes Que Generaron Identificación En La Comunidad Del ‘Templo Del Pueblo’ Con El Líder Jim Jones - Peña Chambo, Angie Lizeth; Barreto Gómez, Sergio Esteban (Universidad Antonio Nariño, 2024)
This research analyzes and describes the unconscious elements that may affect in subjects who are immersed in a religious fanatic mass, using as instrument the method of documentary research from the psychoanalytic theoretical border. An important question analyzed inside this writing is to know: why does a religious community become a fanatical worship? For that reason, a characterization of the mass is realized, using as object of study the case of the People's Temple and its leader Jim Jones. According to this idea, the present text also examines the power that the leader has in the group, taking into account the socio-cultural, the religious beliefs and the unconscious factors that produce the fanatics‘ identification with their leader.